The Dynamics of Social Conflict Over Agricultural Land in Kerinci, Jambi (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2021)
This study analyzes the conflict between migrant cultivators and local cultivators in Tamiai Village, Batang Merangin District, Kerinci Regency, Jambi Province related to land cultivation rights. It is due to the unclear contents of the initial agreement letter, causing conflicts over land disputes between the two community groups. This research is qualitative research with a descriptive-analytical method. Data were collected through interviews and documentation studies. The results of this study reveal that there are several interests and needs of the two conflicting parties related to land management. The interests of local cultivators include protecting the rights of indigenous peoples, maintaining Ulayat land as the identity of the alliance, and clarifying the status of the land. The need for local cultivators is to get economic resources. Meanwhile, the interests of migrant cultivators are to obtain compensation after the conflict and the legality of the land. The needs of migrant cultivators include maintaining economic resources (livelihoods). Among the positive forces influencing conflict resolution are local government mediation and written evidence of land clearing permits. In contrast, the opposing forces that affect conflict resolution are the presence of the parties as provocateurs, the increase in land values, legal uncertainty regarding land status, and poor communication between the conflicting parties.